2020
DOI: 10.2147/ijwh.s240608
|View full text |Cite
|
Sign up to set email alerts
|

<p>Maternal Delays for Institutional Delivery and Associated Factors Among Postnatal Mothers at Public Health Facilities of Gamo Zone, Southern Ethiopia</p>

Abstract: Background: Maternal health delays like delay in deciding to seek care, reaching a health facility, and receiving appropriate care were identified as the main contributing factors for maternal mortality and morbidity in many developing countries including Ethiopia. However, little is known about the magnitude and factors predisposing for maternal health delays in Ethiopia especially in a rural part of the country. Therefore, the aim of this study is to assess the magnitude of maternal delays for institutional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
34
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 20 publications
14
34
2
Order By: Relevance
“…The current study revealed that 59.7% of mothers had delays during emergency obstetric care. The proportion of to emergency obstetric care was high as compared to the first (46.80%), second (44.00%), and third (31.70%) maternal delays in Gamo Zone, Southern Ethiopia [ 34 ]. On the other hand, the delay during emergency obstetric care was lower than in other studies conducted in Yem-special Woreda [ 29 ], Pakistan [ 32 ], and Mozambique [ 33 ] which were 76.3%, 70%, and 69.7%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study revealed that 59.7% of mothers had delays during emergency obstetric care. The proportion of to emergency obstetric care was high as compared to the first (46.80%), second (44.00%), and third (31.70%) maternal delays in Gamo Zone, Southern Ethiopia [ 34 ]. On the other hand, the delay during emergency obstetric care was lower than in other studies conducted in Yem-special Woreda [ 29 ], Pakistan [ 32 ], and Mozambique [ 33 ] which were 76.3%, 70%, and 69.7%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It may have an effect on their delivery service utilization and contribute to the high proportion. It may be due to a lack of skill among health care providers and a disrespectful service delivery system [ 34 ]. The other possible reasons may be lack of women empowerment for early decision-making autonomy, poor physical access to health facilities that provide safe delivery service, poor road construction, and lack of access to health education regarding complications during labor and delivery [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained by the fact that the first dose (BCG and OPV0) of routine immunization is provided immediately after delivery, which may increase maternal awareness and motivate mothers to complete the sequential doses [ 74 ]. Besides, home delivery if taken as a proxy for women’s decision-making autonomy on child’s healthcare may reflect its negative influence on child’s immunization coverage [ 75 , 76 ]. Another study also showed that women that had decision-making autonomy were more likely to utilize both institutional delivery, postnatal follow-ups, and child healthcare services [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second maternal delay: was a time after decision-making to reach health facilities. The time has been estimated at more than one hour to reach the existing health facility and otherwise not [ 16 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…Third maternal delay: was the interval of time between reaching the health facility and accessing the services needed. It took more than 1 hour to receive a delivery service deemed delay and less than an hour deemed no delay [ 33 ].…”
Section: Methodsmentioning
confidence: 99%